APPLICATION OF THE JOURNALISTIC CODE OF ETHICS ON THE PROTECTION OF SEXUAL VIOLENCE NEWS SOURCE AT “LIPUTAN6.COM” - Marcella Putri Cahyani; regina sofya; W Wahyunengsih (Yayasan Hurriah, Banda Aceh, 2022)
This article is a research article related to the application of a journalistic code of ethics to sexual violence news sources at